p5.js Sebagai Medium Inklusif Dalam Praktik Seni Generatif Pada Pendidikan Seni - Ratnasari, Devi; Welayana, Anitalia Stefany; Firmansyah, Arya (Institut Seni Indoensia Surakarta, 2025)
The rapid development of digital technology has opened new opportunities in both art practice and education, one of which is through code-based generative art. However, for art students, programming is often perceived as a barrier due to its complexity and lack of beginner-friendly accessibility. This study aims to explore p5.js as an inclusive medium in generative art practice, focusing on the creation of algorithm-based visual works. The research employs a practice-based research approach, where the creation process is carried out through a series of algorithmic experiments involving iteration, branching, transformation, randomness, and mathematical functions. Each experiment produces visual outputs that are documented and reflectively analyzed to understand the relationship between algorithmic structures and the resulting aesthetic outcomes. The findings show that p5.js, with its simple, web-based, and easily accessible interface, is effective as an inclusive medium for learning generative art. This process not only produces representative artworks but also demonstrates how algorithms can function as a visual language that bridges art and technology within the context of art education.